Metode Pengembangan Media Pembelajaran Model True or False Physics Fun Game Card - Sepriana Leo; Diane Noviandini; Alvama Pattiserlihun (Radiasi : Jurnal Berkala Pendidikan Fisika, 2018)
Abstract - Physics learning is still considered as learning that is less attractive to some students. Students’ lack of learning interest in physics learning makes their achievement low. The purpose of this study was to develop a learning media of True or False Physics Fun Game Card, so as to make the students interested in learning physics which could increase students' interest and learning achievement. The kind of the card game "True or False Physics Fun Game Card" was developed from a 41 card game which was modified as needed. In True or False Physics Fun Game Card, there were 50 true and false statements. Moreover, there were also points of 10-25 based on the level of difficulty of the statements. The statements made based on the Hydrostatic Law, the Relating Vessel, and the Archimedes Law. The True or False Physics Fun Game Card was developed by using the ADDIE development model which consists of 5 development steps, such as analyzing, designing, development, implementation, and evaluation. This study was tested on 12 samples of the Physics students of Universitas Kristen Satya Wacana. The data obtained were processed qualitatively and quantitatively. Based on the results of this study, it was found that 93.75% of students responded positively toward the learning media “True or False Physics Fun Game Card” and the average value of the students' post-test results was 72.67. The 10 samples from a total of 12 test samples obtained the post-test result; 65, so as the percentage of the successful comprehension sample was 83.33%. This study contributed to increasing kinds of learning media and improving students' learning achievement, especially in physics learning.